2017
DOI: 10.17511/ijmrr.2017.i01.05
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of breast lesions

Abstract: Objectives: To study the histopathological features of neoplastic and non neoplastic lesions of breast. To correlate the pathological findings with clinical parameters. Design and methods: We have studied total 161 cases of breast lesions over a period of two years in our institute. The specimens were received in histopathology section of our department. Detailed gross examination of specimens was done followed by fixation, thorough sampling, and tissue processing. The different lesions were studied by histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 10 publications
11
10
0
Order By: Relevance
“…Most of the benign tumors were found in reproductive age group; the present study noted the frequency of occurrence of fibroadenoma to be 90.08% of all benign tumors, which was similar to that reported by Mudholkar et al 5 i.e. 87.40% and much higher than 78.94% reported by Sulhyan et al 4 . The second common benign tumor observed in our study was benign phylloid tumor, comprising 4.58% out of all benign tumors.…”
Section: Histopathological Diagnosis: Neoplastic Lesionssupporting
confidence: 91%
See 1 more Smart Citation
“…Most of the benign tumors were found in reproductive age group; the present study noted the frequency of occurrence of fibroadenoma to be 90.08% of all benign tumors, which was similar to that reported by Mudholkar et al 5 i.e. 87.40% and much higher than 78.94% reported by Sulhyan et al 4 . The second common benign tumor observed in our study was benign phylloid tumor, comprising 4.58% out of all benign tumors.…”
Section: Histopathological Diagnosis: Neoplastic Lesionssupporting
confidence: 91%
“…In the present study, we observed that, maximum number of cases of benign breast tumors occurred between 11-20 years, followed by 3rd decade. Sulhyan KR et al 4 4 and sharma K et al 8. In present study, left breast involvement was more common than right (51.83%); this observation agreed with that of the other authors 10,11. Most common location for breast lesion was upper outer quadrant; the observations in the present study (45.85%) concurred with those reported previously 4,5 11.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that maximum number of cases occurred between 14-24 years, Sylhan et al, reported maximum number of cases occurred between 11-20 years followed by 3 rd and 4 th decade. 2 Fibroadenoma with Infarction was found in one case. Varghas et al, reported infarcted myxoid fibroadenoma following fine needle aspiration.…”
Section: Discussionmentioning
confidence: 92%
“…Sulhyan et al, reported incidence of 2.5% cases Olu Eddo et al, reported incidence of 2%. 2,18 Haque et al, reported an incidence of 8.66% and average age of 20 years. 4 Johnson et al, stated that initial first step should be ruling out pseudogynecomastia by history taking and physical examination.…”
Section: Non-neoplastic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation